The Pope of Physics Enrico Fermi and the birth of the atomic age - Segrè, Gino 1938-; Hoerlin, Bettina 1939- (Henry Holt and Company, 2016)
"The first full-scale biography of the Nobel Prize-winning physicist and one of the fathers of the atomic age, Enrico Fermi. Enrico Fermi is unquestionably the most famous scientist to come from Italy since Galileo, so revered that he's known as The Pope of Physics. A modest, unassuming man, Fermi was nevertheless one of the most productive and creative scientists of the twentieth century, one of the fathers of the Atomic Bomb and a Nobel Prize winner whose contributions to physics and nuclear technology live on today, with the largest particle accelerator in the United States and the nation's most significant science and technology award both bearing his name. In this, the first major biography of Fermi in English, Gino Segre, professor of Physics and Astronomy at the University of Pennsylvania, brings this scientific visionary to life. An examination of the human dramas that touched Fermi's life as well as a thrilling history of scientific innovation in the twentieth century...including the birth of one of its most controversial disciplines, nuclear physics...this is the comprehensive biography that Fermi deserves"...